High Glucose and Lipopolysaccharide Prime NLRP3 Inflammasome via ROS/TXNIP Pathway in Mesangial Cells - Hong Feng; Junling Gu; Fang Gou; Wei Huang; Chenlin Gao; Guo Chen; Yang Long; Xueqin Zhou; Maojun Yang; Shuang Liu; Shishi Lü; Qiaoyan Luo; et al. (Journal of Diabetes Research)
While inflammation is considered a central component in the development in diabetic nephropathy, the mechanism remains unclear. The NLRP3 inflammasome acts as both a sensor and a regulator of the inflammatory response. The NLRP3 inflammasome responds to exogenous and endogenous danger signals, resulting in cleavage of procaspase-1 and activation of cytokines IL-1β, IL-18, and IL-33, ultimately triggering an inflammatory cascade reaction. This study observed the expression of NLRP3 inflammasome signaling stimulated by high glucose, lipopolysaccharide, and reactive oxygen species (ROS) inhibitor N-acetyl-L-cysteine in glomerular mesangial cells, aiming to elucidate the mechanism by which the NLRP3 inflammasome signaling pathway may contribute to diabetic nephropathy. We found that the expression of thioredoxin-interacting protein (TXNIP), NLRP3, and IL-1β was observed by immunohistochemistry in vivo. Simultaneously, the mRNA and protein levels of TXNIP, NLRP3, procaspase-1, and IL-1β were significantly induced by high glucose concentration and lipopolysaccharide in a dose-dependent and time-dependent manner in vitro. This induction by both high glucose and lipopolysaccharide was significantly inhibited by N-acetyl-L-cysteine. Our results firstly reveal that high glucose and lipopolysaccharide activate ROS/TXNIP/ NLRP3/IL-1β inflammasome signaling in glomerular mesangial cells, suggesting a mechanism by which inflammation may contribute to the development of diabetic nephropathy.